Mechanical characteristics and microstructural changes in phosphogypsum-cement-lime composite modified loess - Jin Chang; Jue Li; Yudan Wang; Haina Zhang (Case Studies in Construction Materials)
Loess is widely distributed in China but suffers from inherent deficiencies limiting its direct use as a subbase material in road construction without modifications. This study investigated the utilization of Phosphogypsum (PG), an industrial waste, in a composite stabilizer containing cement, lime and slag powder for modifying loess in the subbase application. An orthogonal test design was employed to optimize the composite proportions. Laboratory tests evaluated the mechanical properties including unconfined compressive strength (UCS), splitting tensile strength, resilient modulus and water stability of modified loess over curing periods up to 90 days. Microstructural evolution was analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results showed the composite containing 25 % PG, a cement-slag ratio of 4:6 and 5 % lime imparted the highest strengths. Mechanical performances increased with curing time and stabilizer content. Water stability and heavy metal immobilization were satisfactory. Microstructural results revealed microstructural densification occurred through hydration product development binding soil particles. This work demonstrated the technical and environmental viability of recycling PG through loess improvement, offering a sustainable solution for problematic soil stabilization and industrial waste utilization.